Using a Spectrofluorometer for Resonance Raman Spectra of Organic Molecules - Vadivel Masilamani; Hamid M. Ghaithan; Mamduh J. Aljaafreh; Abdullah Ahmed; Reem al Thagafi; Saradh Prasad; Mohamad S. Alsalhi (Journal of Spectroscopy)
Scattering (Rayleigh and Raman) and fluorescence are two common light signals that frequently occur together, confusing the researchers and graduate students experimenting in molecular spectroscopy laboratories. This report is a brief study presenting a clear discrimination between the two signals mentioned, employing a common spectrofluorometer such as the PerkinElmer LS 55. Even better, the resonance Raman signal of a molecule (e.g., acetone) can be obtained elegantly using the same instrument.